Nuovi territori per una nuova sostenibilità: la rigenerazione territoriale - Patrizio, Carlo (Scienze del Territorio, 2015)
The territorial regeneration Plan “Ricominciodatré” is an integrated project. It contains not only expectations about town planning or construction, but even intangible measures on the system of cultural services. Three towns of Salento, Veglie, Salice Salentino and Carmiano, formed a group to define a plan focused on the theme of cinema, theatre, visual arts and audiovisual, with the aim to directly produce cine-cultural entertainment activities. In Carmiano, the plan provides to the recovery of a historic movie theatre, cinema Empire, and of the square. Here, activities strictly linked to cinema and theatre will take place. In Veglie, the raising of “Tramacère house” has been designed with the intention to put in its ground floor the seat for associations and, in its first floor, spaces dedicated to arthouse films and film club. Finally in Salice, in the Madonna della visitazione convent it is expected to place laboratory activities about film production and the “Memory lab”. The Plan has got the objectives to promote: revitalization of the social fabric; development of envi-ronmental and cultural tourism, etc..; attractiveness and competitiveness of all the territories; quality of cultural offer; inclusion of the most vulnerable classes; activities that act as fuel for connections and relationships between the residents and their ‘cultural’ environment.